Improving Learning Achievement of Plane Materials Through Tangram Media Using the Project Based Learning Model - Krisdayanti, Irene; Murtafiah, Wasilatul; Kholifah, Titik Siti; Yahya, Faridah Hanim (IndoMath: Indonesia Mathematics Education, 2023)
Learning mathematics that emphasizes understanding concepts and solving problems requires learning media. The use of learning media is still low, so learning outcomes are far from the minimum completeness criteria (the student's lowest score), apart from learning media. Besides the media, learning models are essential to discover fun and not dull mathematics. This study aimed to improve learning achievement in data-building material through tangram media with the PjBL model for class IV at SD Negeri Gerih 7, East Java, Indonesia. The research method used was Collaborative Classroom Action Research. The subjects of this study were 23 students in grade IV at SD Negeri Gerih 7, East Java, Indonesia, in the 2022/2023 academic year. The test results obtained were in the form of pre-cycle class average values of 59.13, 64.78 in the results of the first cycle, and 77.82 in the results of the second cycle. It can be concluded that the PjBL learning model and the tangram media effectively improve the achievement results of fourth-grade students at SD Negeri Gerih 7, East Java, Indonesia.